Consumo de álcool e dislipidemias em participantes do estudo longitudinal de saúde do adulto ELSA-BRASIL - Martinez, Oscar Geovanny Enriquez (2018)
Dyslipidemias are defined as a change in the functioning of lipoproteins, such as Total Cholesterol (CT), HDL Cholesterol (HDL-c), LDL Cholesterol (LDL-C) and Triglycerides (TGS). Several factors are involved in its genesis, and there are still constroversias about the effect of alcohol consumption on the dyslipidemic. In Brazil, alcohol abuse increased by 3.4% in 10 years. The objective of this study was to investigate the relationship between alcohol consumption, as well as the type of alcoholic beverage, and lipid parameters in ELSA-Brasil participants. A baseline sample (2008-2010), aged 35-74, of both sexes was studied. Sociodemographic, lifestyle, biochemical and anthropometric data were collected in a standardized way in six teaching and research institutions The consumption of alcoholic beverages was estimated in dose / week and categorized in tertiles (1-7, 7-14 and> 14 doses / week) and by type of drink (beer, wine and spirits). Lipid parameters were used as continuous data. Linear regression models for each type and total of alcoholic beverages were tested. A significance level of 5% was accepted. A total of 12,179 participants were studied, 55.7% were women, 41.3% were 45-54 years old, 53.4% were superior, and 69.8% reported consuming alcoholic beverages. A significant association was found between CT, TGS and HDL-c and total alcohol consumption, but not with LDL-c. When analyzed by type of alcoholic beverage, it was observed that all lipid parameters increased with the increase in the number of doses / week of beer. It was also observed that consumption of 1-7 doses / week of wine significantly increased TC. Consumption between 1-7 and 7-14 doses / week elevated HDL-c. No association was observed with TGS and LDL-c. Consumption of spirits drinks of 1-7 and 7-14 doses / week increased CT. It was observed increased HDL-C in all categories of beverage consumption spirits. It is concluded that the total consumption of alcoholic beverages and beer increased all the biochemical parameters evaluated. Wine consumption increased all parameters, with the exception of TGS.